Neuromuscular control and performance in shot-put athletes. - Terzis, G.; Karampatsos, G; Georgiadis, G (J Sports Med Phys Fitness, 2007)
AIM: The aim of this study was to investigate the relationship between the activation level of certain protagonist muscles of the upper and lower body during the shot-put with the shot-put performance in skilled athletes. METHODS: Eight experienced right-handed shot-putters, performed the shot-put with the linear technique. They also performed a maximum (1RM) squat and a 1RM incline bench-press strength test. Electromyographic (EMG) signals were recorded from the m. quadriceps vastus lateralis (VL), m. gastrocnemius internus, m. pectoralis major (PEC) and the m. triceps brachii (TRI) of the right side during all efforts. The level of EMG during the shot-put was normalized relatively to that measured during the respective maximum strength test. RESULTS: Shot-put performance was significantly correlated with 1RM squat (r=0.76, P<0.05) and 1RM bench-press (r=0.75, P<0.05) as well as with the average EMG from VL and PEC after taking the power position (r=0.91, P<0.01 and r=0.75, P<0.05, respectively). A close negative relationship was also found between shot-put performance and the time to reach peak activation of right TRI during the explosive strike of the throwing arm (r=-0.70, P<0.05). CONCLUSION: These results suggest that, besides the importance of absolute muscle strength, an important parameter for shot-put performance is the level of activation of the VL and the PEC during the delivery phase. Furthermore, these data suggest that the TRI should be activated fast in order to be an effective contributor to the shot-put performance.
Keywords: Adult; Biomechanical Phenomena; Electromyography; Exercise Test; Humans; Male; Muscle Contraction; Muscle, Skeletal; Prospective Studies; Sports Medicine; Task Performance and Analysis; Track and field